2004
DOI: 10.1111/j.1439-0272.2004.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

The male reproductive system and its susceptibility to endocrine disrupting chemicals

Abstract: Summary.  In the past years, there has been increased interest in assessing the relationship between impaired male fertility and environmental factors. Human male fertility is a complex process and therefore a great variety of sites may be affected by exogenous noxae. Lifestyle factors as well as various environmental and occupational agents may impair male fertility. Many studies have been published reporting on reproductive dysfunctions in male animals and humans. Especially environmental pollutants with end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(68 citation statements)
references
References 78 publications
2
63
0
3
Order By: Relevance
“…These plastics can be used in baby bottles, water storage tanks, or supply pipes (5). It is also used to make epoxy resins, electronics, medical equipments, and dental sealants (6,7). The human population is frequently exposed to BPA through various sources.…”
Section: Introductionmentioning
confidence: 99%
“…These plastics can be used in baby bottles, water storage tanks, or supply pipes (5). It is also used to make epoxy resins, electronics, medical equipments, and dental sealants (6,7). The human population is frequently exposed to BPA through various sources.…”
Section: Introductionmentioning
confidence: 99%
“…The leading hypothesis for these growing concerns is that certain chemicals, used in plastics to provide beneficial physical qualities, may also act as endocrine-disrupting compounds (EDCs) that could lead to adverse reproductive and developmental effects (NRC 1999). In men, environmental or occupational exposures to EDCs may be associated with or lead to declined reproductive capacity or possibly increased risk of testicular or prostate cancer (Fleming et al 1999;Pflieger-Bruss et al 2004;Toft et al 2004). In fact, a number of studies have suggested the use of circulating reproductive hormone levels (follicle-stimulating hormone (FSH) and/or inhibin B) as a surrogate measure for semen quality or fecundity in epidemiologic studies ( Jensen et al 1997;Uhler et al 2003;Mabeck et al 2005), although other recent studies suggest hormone levels may lack sufficient ability to predict poor semen quality (Dhooge et al 2007;Meeker et al 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…(Richter et al, 2007) The issue with BPA is that studies have been published with both no observed effects and significant observed effects in both mice and rats for dosages below the "safe dose". (Pflieger-Bruss et al, 2004) A review published in 2005, (vom Saal & Hughes, 2005) discusses the existence of both results in published studies but proceeds to make several important points regarding the proportions of the opposing results. In the review by vom Saal (vom Saal & Hughes, 2005), the author discusses a large inconsistency in the data with regards to the source of funding for each study.…”
Section: Figurementioning
confidence: 99%
“…A study completed by Pflieger-Bruss et al (2004)outlined the common effects of xeno-estrogen compounds, (i.e. BPA and DES) in animal studies as hypospadias, cryptorchidism, decreased sperm count and testicular tumours.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation